Character Education Values in Surah Ash-Shaffat Verses 102–110 According to M. Quraish Shihab’s Interpretation in Tafsir Al-Misbah - Firdaus, Firdaus; Suryani, Suryani; Karnedi, Rozian (FKIP - Universitas Riau, 2025)
This study is driven by a moral crisis within the contemporary Islamic education system, particularly in the realm of character education, which calls for reconstructing value-based learning rooted in the Qur’an. This condition indicates a reasoning gap in comprehending and implementing character values that align with current global realities. The objective of this research is to analyze M. Quraish Shihab’s interpretation of Surah Ash-Shaffat (verses 102–110), to examine the distinctive style and thematic orientation of Tafsir Al-Misbah, and to identify the embedded values of character education found within these verses. This study employs a qualitative approach using library research, with data collected from primary sources—namely, Tafsir Al-Misbah—and supported by secondary references related to Qur’anic interpretation and Islamic education. The findings reveal three key points: (1) the verses illustrate the exemplary character of Prophet Ibrahim and Prophet Ismail in their patience, spiritual resilience, and obedience to divine commands; (2) the interpretive model of Tafsir Al-Misbah adopts a socio-cultural and literary approach with an emphasis on the relevance of Qur’anic teachings in daily life; and (3) character values identified include faith, respect, responsibility, compassion, and sincerity. These values are fundamental in constructing a character education framework that reflects Qur’anic principles and addresses the challenges of modern Islamic education.